Should Archaeology Have a Future? - Wurst, LouAnn (Journal of Contemporary Archaeology, 2019)
Archaeologists have recently been discussing what the future may hold for archaeology, a focus firmly situated within the context that the discipline of archaeology is authentic and legitimate and deserves to have a future. In this paper, I want to challenge these ideas and think instead about whether archaeology should even have a future. This line of reasoning is developed by examining the relationship between capitalism and the academy, neoliberal transformations to higher education, and some of the ways that archaeologists have responded. I conclude with some suggestions for alternatives, both for those working within the dominant capitalist academic structures themselves and those that eschew capitalism itself.